Cynaropicrin- and chlorogenic acid-rich extracts easily prepared from Cynara cardunculus var. scolymus: antioxidant and antigenotoxic properties - Gonçalves, Ana (2023)
Cynara cardunculus L. var. scolymus, commonly known as globe artichoke, is known for its medicinal and culinary properties since ancient times. Nowadays, with the increasing demand for healthier foods artichoke has been valorized and worldwide production has increased to meet the increasing demand in consumption of the flower and infusion from leaves. The aim of this work was to characterize the main bioactive compounds obtained from artichoke leaf extracts using simple and sustainable techniques. Among different extraction procedures tested, decoction in water gave extracts particularly rich in chlorogenic acid (1) and cynaropicrin (2) as demonstrated by the NMR spectroscopy analysis. Compounds 1 and 2 were efficiently separated by liquid-liquid extraction, as 1 was only found in the aqueous (Aq) fraction and 2 was selectively isolated in the organic (O) fraction. While both fractions showed in vitro antioxidant activity by scavenging activity, only the O fraction was able to protect Saccharomyces cerevisiae cells from oxidative stress. Interestingly, the O fraction was much more antigenotoxic than Aq fraction, suggesting a highly efficient hydroxyl radical scavenging activity. Besides being simple and avoiding organic solvents, decoction in water provides maximal extraction of 1 and 2 and, presumably, maximal bioactivities.